A new wave in Romania: organic food. Consumers' motivations, perceptions, and habits. Issue 1 (2nd January 2017) - Petrescu, Dacinia Crina; Petrescu-Mag, Ruxandra Malina; Burny, Philippe; Azadi, Hossein
ABSTRACT: This study is based on a probabilistic survey and adopts an original approach—by putting dual focus on certified and uncertified organic products—to draw a profile of Romanian consumers of organic food. Uncertified organic food (from farmers' market or self-production) is considered to be more "organic" than certified organic food. While consumers are strongly oriented toward organic food (certified or uncertified) and driven by health concerns and taste, they are primarily deterred by price and lack of availability. Results show that, to develop a sustainable market, consumers' extended and positive evaluations of uncertified organics represent the link to initiate the behavioral transition from conventional to certified organic food.